"Speculated Communities": The Contemporary Canadian Speculative Fictions of Margaret Atwood, Nalo Hopkinson, and Larissa Lai - Hildebrand, Laura A (Université d'Ottawa / University of Ottawa, 2012)
Speculative fiction is a genre that is gaining urgency in the contemporary Canadian literary scene as authors and readers become increasingly concerned with what it means to live in a nation implicated in globalization. This genre is useful because with it, authors can extrapolate from the present to explore what some of the long-term effects of globalization might be. This thesis specifically considers the long-term effects of globalization on communities, a theme that speculative fictions return to frequently. The selected speculative fictions engage with current theory on globalization and community in their explorations of how globalization might affect the types of communities that can be enacted. This thesis argues that these texts demonstrate how Michael Hardt and Antonio Negri’s notion of “cooperative autonomy” can be uniquely cultivated in the conditions of globalization – despite the fact that those conditions are characterized by the fragmentation of traditional forms of community (Empire 392).
Keywords: Speculative fiction; Science fiction; Canadian literature; Globalization; Genre; Cooperative autonomy; Atwood, Margaret; Hopkinson, Nalo; Lai, Larissa